Phronesis and Authenticity as Keywords for Philosophical Praxis in Teacher Training - Hansen, Finn Thorbjorn (Paideusis, 2007)
This essay describes the growing interest in and use of concepts such as phronesis and authenticity in educational research and practice. While phronesis seems to be connected to the ethical dimension of education and educational guidance, the concept of authenticity seems to be connected to the existential dimension. This essay shows the relatedness between those two concepts and the relevance of an “existence philosophical” perspective on phronesis and authenticity. The author points to the importance of an ontological approach where phronesis and authenticity are understood as two ways of respectively sensing and understanding the Being-dimension. This existence philosophical approach opens up for a new kind of praxis of Philo-Sophia, which could be realized in teacher training, when the focus is on how to become more mindful and aware of the Bildung-process in education and guidance. The essay suggests that this Being-dimension can be approached through the emergence of Communities of Wonder between the teacher and teacher student in the classroom or guidance session.